Psychiatric Comorbidities and Liver Injury Are Associated With Unbalanced Plasma Bile Acid Profile During Methamphetamine Withdrawal - Ma, Yuru; Wu, Hongjin; Wang, Huawei; Chen, Fengrong; Xie, Zhenrong; Zhang, Zunyue; Peng, Qingyan; Yang, Jiqing; Zhou, Yong; Chen, Cheng; Chen, Minghui; Zhang, Yongjin; et al. (Frontiers in Endocrinology, 2022)
Background The pathogenesis of methamphetamine usedisorders (MUDs) remains largely unknown; however, bile acids may play arole as potential mediators of liver injury and psychiatric comorbidities.The aim of this study was to characterize bile acid (BA) profiles in plasmaof patients with MUDs undergoing withdrawal. Methods Liver functions and psychiatric symptoms wereevaluated in a retrospective cohort (30 MUDs versus 30 control subjects) andan exploratory cohort (30 MUDs including 10 subjects each at the 7-day,3-month, and 12-month withdrawal stages versus 10 control subjects). BAcompositions in plasma samples from MUD patients in the exploratory cohortwere determined by gas-liquid chromatography. Results Both psychiatric comorbidities andmethamphetamine-induced liver injury were observed in patients in both MUDcohorts. The plasma concentrations of the total BA, cholic acid (CA), andchenodeoxycholic acid (CDCA) were lower in MUD patients relative tocontrols. The maximum decline was observed at the 3-month stage, withgradual recovery at the 12-month stage. Notably, the ratios of deoxycholicacid (DCA)/CA and lithocholic acid (LCA)/CDCA were statistically significantat the 3-month stage comparing with controls. Significant correlations werefound between the LCA/CDCA and taurolithocholic acid (TLCA)/CDCA ratios andthe levels of alanine transaminase and aspartate aminotransferase, andbetween the LCA/CDCA ratio and the HAM-A score. Conclusion BA profile during METH withdrawal weremarkedly altered, with these unbalanced BAs being associated with liverinjury. The associations between BA profiles and psychiatric symptomssuggest an association between specific BAs and disease progression,possibly through the liver-brain axis.